Recombinant human G6PD for quality control and quality assurance of novel point-of-care diagnostics for G6PD deficiency - Kahn, Maria (PLoS One, 2017)
BACKGROUND: A large gap for the support of point-of-care testing is the availability of reagents to support quality control (QC) of diagnostic assays along the supply chain from the manufacturer to the end user. While reagents and systems exist to support QC of laboratory screening tests for glucose-6-phosphate dehydrogenase (G6PD) deficiency, they are not configured appropriately to support point-of-care testing. The feasibility of using lyophilized recombinant human G6PD as a QC reagent in novel point-of-care tests for G6PD deficiency is demonstrated. METHODS: Human recombinant G6PD (r-G6PD) was expressed in Escherichia coli and purified. Aliquots were stored at -80°C. Prior to lyophilization, aliquots were thawed, and three concentrations of r-G6PD (representing normal, intermediate, and deficient clinical G6PD levels) were prepared and mixed with a protective formulation, which protects the enzyme activity against degradation from denaturation during the lyophilization process. Following lyophilization, individual single-use tubes of lyophilized r-G6PD were placed in individual packs with desiccants and stored at five temperatures for one year. An enzyme assay for G6PD activity was used to ascertain the stability of r-G6PD activity while stored at different temperatures. RESULTS: Lyophilized r-G6PD is stable and can be used as a control indicator. Results presented here show that G6PD activity is stable for at least 365 days when stored at -80°C, 4°C, 30°C, and 45°C. When stored at 55°C, enzyme activity was found to be stable only through day 28. CONCLUSIONS: Lyophilized r-G6PD enzyme is stable and can be used as a control for point-of-care tests for G6PD deficiency.